2021
DOI: 10.1249/mss.0000000000002596
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Cardiometabolic Health Indicators after HIIT in Patients with Coronary Artery Disease

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 52 publications
0
17
1
Order By: Relevance
“…Our meta-analysis in patients with coronary artery disease revealed smaller absolute improvements in VȮ 2 peak, BMI and fasting plasma glucose in females than males following HIIT (Way et al 2021). Given the analysis revealed an 8-fold greater participation of males than females, additional data in females is needed (Way et al 2021). In contrast, in an analysis of randomized trials (only 8 females and 19 males engaged in HIIT), VȮ 2 peak in mL/kg/min improved similarly in both sexes (Trachsel et al 2020).…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations
“…Our meta-analysis in patients with coronary artery disease revealed smaller absolute improvements in VȮ 2 peak, BMI and fasting plasma glucose in females than males following HIIT (Way et al 2021). Given the analysis revealed an 8-fold greater participation of males than females, additional data in females is needed (Way et al 2021). In contrast, in an analysis of randomized trials (only 8 females and 19 males engaged in HIIT), VȮ 2 peak in mL/kg/min improved similarly in both sexes (Trachsel et al 2020).…”
Section: Introductionmentioning
confidence: 64%
“…There is a paucity of sex-based evaluations of HIIT (Lee et al 2018;Terada et al 2019a;Rengo et al 2020;Trachsel et al 2020;Way et al 2021). Our primary finding aligns with an analysis of randomized trials including MICT and HIIT which did not find time by sex interactions in VȮ 2 peak with (∆ females: 1.9±2.5; males: 2.9±3.5 mL/kg/min, p=0.255) or without (∆ females: 1.1±2.1; males: 2.0±2.6 mL/kg/min, p=0.116) lean body mass adjustment (Trachsel et al 2020).…”
Section: ))mentioning
confidence: 99%
See 2 more Smart Citations
“…Pattyn et al found HIIT protocols that were isocaloric with MICT were more likely to show superiority over MICT (+2.1 mL/kg/min) compared with HIIT protocols that were a lower energy expenditure to MICT (+0.2 mL/kg/min) (52). Furthermore, Way et al (83) demonstrated that although women tend to experience lower absolute improvements in VO 2 peak with HIIT than men, they have similar relative improvements in VO 2 peak (83) . The FITR Heart Study, a recently published pragmatic trial in 93 CAD patients using RPE as the primary method of exercise prescription (36), also demonstrated a superior effect of HIIT compared with MICT during a 4-week CR program, with a mean difference in VO 2 peak improvement of 1.7 mL/kg/min.…”
Section: Influence Of Exercise Intensity On Cvd and Mortalitymentioning
confidence: 99%